2021
DOI: 10.1002/npr2.12158
|View full text |Cite
|
Sign up to set email alerts
|

The neural differences of arithmetic verification performance depend on math skill: Evidence from event‐related potential

Abstract: Aim Math skill is a basic need for an individual, as a career prospect. However, little is known about early brain processes of arithmetic between individuals with different math skill. Therefore, we questioned the modulation of the amplitude of an early negative component by math skill level in an arithmetic verification paradigm using event‐related potential (ERP). Methods Thirty‐six right‐handed participants were assigned in two groups of high‐ and low‐performing students. Their electroencephalogram was rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In terms of attention level data collection and processing, most scholars used various questionnaires, scales, or experimental measurement methods, such as short‐term memory recall (Knez & Hygge, 2002), word repetition (LaPointe et al, 2005), the “Go/No‐go” task, the paced visual serial addition task (PVSAT) (Cui et al, 2022), and the numerical verification (NV) task (Taghizadeh et al, 2021). Since attention is a complex neurological and psychological phenomenon involving many different brain structures and mechanisms, it is impossible to measure a subject's attention level directly and quickly solely using questionnaires, scales, or experimental measurements, while instant inspection and feedback are impossible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of attention level data collection and processing, most scholars used various questionnaires, scales, or experimental measurement methods, such as short‐term memory recall (Knez & Hygge, 2002), word repetition (LaPointe et al, 2005), the “Go/No‐go” task, the paced visual serial addition task (PVSAT) (Cui et al, 2022), and the numerical verification (NV) task (Taghizadeh et al, 2021). Since attention is a complex neurological and psychological phenomenon involving many different brain structures and mechanisms, it is impossible to measure a subject's attention level directly and quickly solely using questionnaires, scales, or experimental measurements, while instant inspection and feedback are impossible.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of attention level data collection and processing, most scholars used various questionnaires, scales, or experimental measurement methods, such as short-term memory recall (Knez & Hygge, 2002), word repetition (LaPointe et al, 2005), the "Go/No-go" task, the paced visual serial addition task (PVSAT) (Cui et al, 2022), and the numerical verification (NV) task (Taghizadeh et al, 2021).…”
mentioning
confidence: 99%
“…Similarly, the arithmetic ERP effect was thought to reflect sentence-like comprehension of the multiplication facts, where the operands facilitate access to the correct solution resulting in a reduction of N400 amplitude . This interpretation of this arithmetic N400 was adopted in many subsequent studies (Domahs et al, 2007;Jost et al, 2004;Salillas & Wicha, 2012;Szucs & Csépe, 2004;Szucs & Soltész, 2010;Taghizadeh et al, 2021).…”
Section: Arithmetic Processing and Event-related Potentials (Erps)mentioning
confidence: 99%
“…In addition to the fMRI, evoked (phase-locked) and induced (non-phase-locked) activities in the electroencephalography (EEG) pattern have highlighted neurophysiological patterns of mental subtraction in the human brain. The event-related potential (ERP) results were employed to identify several negative components between 200 ms and 400 ms in subtraction that have been referred to as N200, N270, N300, P300 and N400, compared with addition or multiplication (Jasinski and Coch 2012 ; Taghizadeh et al 2021 ; Gao et al 2022 ). The event-related desynchronization and synchronization (ERD/ERS) also revealed that subtractions is associated with a lower theta ERS than multiplication in the frontal and parietooccipital cortices (Brunner et al 2021 ); additionally, it displayed a higher alpha ERD than addition, with the largest difference in the parietooccipital cortex (De Smedt et al 2009a ).…”
Section: Introductionmentioning
confidence: 99%